Influence of variants of Fcγ receptors IIA and IIIA on the American College of Rheumatology and European League Against Rheumatism responses to anti-tumour necrosis factor α therapy in rheumatoid arthritis. Issue 10 (17th October 2008) - Cañete, J D; Suárez, B; Hernández, M V; Sanmartí, R; Rego, I; Celis, R; Moll, C; Pinto, J A; Blanco, F J; Lozano, F
Abstract : Objective: Fcγ receptor (FcγR) polymorphism influences the affinity of the receptor for Ig, which may, in turn, affect the efficacy of Ig-based therapies. The relationship between functional single nucleotide polymorphisms (SNP) of the FCGR2A and FCGR3A genes and the response to anti-tumour necrosis factor (TNF)α therapy (infliximab) in patients with rheumatoid arthritis (RA) was assessed. Methods: A total of 91 patients with RA (89% female; 76.7% rheumatoid factor (RF) positive) starting therapy with infliximab were evaluated at 0, 6 and 30 weeks using the American College of Rheumatology (ACR) and European League Against Rheumatism (EULAR) response criteria and the 28-joint Disease Activity Score (DAS28) was evaluated using three parameters, including C-reactive protein (CRP) (DAS28 3v-CRP) changes during the follow-up. Genotyping of FCGR2A -R131H and FCGR3A -F158V polymorphisms was performed by allele-specific PCR and PCR sequence-based typing, respectively. The χ 2 and Fisher exact tests were used to show differences in the outcome variables, and analysis of variance (ANOVA) to analyse the evolution of DAS28 3v-CRP. A generalised linear models multivariable analysis was also performed. Results: At week 6 of follow-up, the proportion of patients achieving 50% improvement as per ACR criteria (ACR50) and EULAR good responses were significantly higher among homozygotes of the low affinity FCGR3A allele (FF: 24.1% and VV-VF:2.2%; p = 0.003 and FF: 44.8% and VV-VF: 22.9%; p = 0.040, respectively). At week 30, homozygotes of the low affinity FCGR2A allele had a better ACR20 response (RR: 60% and HH-RH: 33.3%; p = 0.035). Changes in DAS28 3v-CRP during follow-up were consistent with those observed in ACR and EULAR responses. Conclusions: The response to anti-TNFα treatment with infliximab in patients with RA is influenced by the FCGR2A and FCGR3A genotypes. This effect is observed at different times in the follow-up (6 and 30 weeks, respectively) indicating the dynamic nature of the FcγR versus Ig interaction.